Psychosocial Pre-Transplant Screening With the Transplant Evaluation Rating Scale Contributes to Prediction of Survival After Hematopoietic Stem Cell Transplantation - Scherer, Simon; Scheid, Christoph; Bergwelt, Michael von; Hellmich, Martin; Albus, Christian; Vitinius, Frank (Frontiers in Psychiatry, 2021)
There is no standard in hematopoietic stem cell transplantations (HSCT) for pre-transplant screening of psychosocial risk factors, e.g., regarding immunosuppressant non-adherence. The aim of this prospective study is to explore the predictive value of the pretransplant psychosocial screening instrument Transplant Evaluation Rating Scale (TERS) for mortality in a three-year follow-up. Between 2012 and 2017 61 patients were included and classified as low (TERS = 26.5–29) and increased-risk group (TERS = 29.5–79.5). Both groups were compared regarding mortality until 36 months after transplantation and secondary outcomes (Medication Experience Scale for Immunosuppressants (MESI); incidence/grade of GvHD). The increased-risk group (n=28) showed significantly worse cumulative survival in the outpatient setting (from three months to three years after HSCT) (Log Rank (Mantel Cox) P=0.029) compared to low-risk group (n=29) but there was no significant result for the interval immediately after HSCT until 3 years afterwards. Pre-transplant screening with TERS contributes to prediction of survival after HSCT. The reason remains unclear, since TERS did not correlate with GvHD or MESI. The negative result regarding the interval immediately after HSCT until 3 years could be caused by the intensive in-patient setting with mortality which is explained rather by biological reasons than by nonadherence.